Consumo de bebidas alcóolicas em binge na adolescência precoce: um estudo transversal - Mariana Oliveira Guimarães (2022)
The aim of this study was to assess the prevalence of binge drinking in early adolescence and its association with the consumption of alcohol mixed with energy drinks, religiosity and social capital. This is a cross-sectional study carried out with adolescents aged 10 to 13 years old enrolled in public schools in Belo Horizonte, Brazil. The random stratified sampling was performed, proportionally by administrative district and by school year. To select students, schools were randomly selected by region and all eligible students were invited to participate. A total of 650 adolescents participated in the study. Adolescents completed the Alcohol Use Disorders Identification Test (AUDIT-C), questions about drinking alcohol mixed with energy drinks, binge drinking by parents and best friend, questions about religiosity, and the social capital questionnaire for adolescents (QSCAE). A form regarding socioeconomic issues was answered by the parents. Descriptive analysis, univariate and multiple logistic regression (p <0.05) were performed. The results were presented in the form of three articles. The first article addressed the association between the consumption of alcoholic beverages mixed with energy drinks and binge drinking, the second article the association between religiosity and binge drinking and the third article the association between social capital and binge drinking. The prevalence of binge drinking was 13.7%. In the adjusted model, consumption of alcohol mixed with energy drinks (OR: 6.13; 95% CI: 3.81-11.83; p< 0.001), binge drinking by the mother (OR: 2.88; CI 95 %: 1.59-5.24; p< 0.001), binge drinking by the best friend (OR: 4.28; 95% CI: 2.35-7.79; p< 0.001) and non-nuclear family (OR: 1.89; 95% CI: 1.03-3.48; p= 0.039) were associated with the outcome. Religiosity was not associated with binge drinking. The associated covariates were age 12-13 years (OR: 1.94; 95% CI: 1.06-3.56; p= 0.030), binge drinking by the mother (OR: 3.07; 95% CI: 1.73-5.46; p < 0.001); binge drinking by best friend (OR: 6.01; 95% CI: 3.40-10.62; p< 0.001) and non-nuclear family (OR: 1.80; 95% CI: 1.01-3.23 ; p=0.045). High social cohesion at school (OR: 0.41; 95% CI: 0.20-0.0.83; p=0.024), high network of friends (OR: 1.02; 95% CI: 0.20-0.83; p=0.013); binge drinking by best friend (OR: 6.21; 95% CI: 3.43-11.23; p<0.001); binge drinking by the mother (OR: 3.26; 95% CI: 1.80-5.89; p<0.001) and lower maternal education (OR: 2.69; 95% CI: 1.52-4.76; p=0.001 ) were associated with the outcome. It was concluded that the consumption of alcohol mixed with energy drinks, the age of 12-13 years, binge drinking by the mother and best friend, lower maternal education, non-nuclear family and high network of friends were factors associated with binge drinking. High school cohesion was a possible protective factor and religiosity was not associated with binge drinking in early adolescence.